Effects of Phytic Acid-Degrading Bacteria on Mineral Element Content in Mice - Zhou, Diao; Zhao, Ying; Li, Jing; Ravichandran, Vinothkannan; Wang, Leli; Huang, Qiuyun; Chen, Cang; Ni, Hengjia; Yin, Jia (Frontiers in Microbiology, 2021)
Trace minerals are extremely important for balanced nutrition, growth, and development in animals and humans. Phytic acid chelation promotes the use of probiotics in nutrition. The phytic acid-degrading strain Lactococcus lactis psm16 was obtained from swine milk by enrichment culture and direct plate methods. In this study, we evaluated the effect of the strain psm16 on mineral elements in a mouse model. Mice were divided into four groups: basal diet, 1% phytic acid, 1% phytic acid + psm16, 1% phytic acid + 500 U/kg commercial phytase. Concentrations of acetic acid, propionic acid, butyric acid, and total short-chain fatty acids were significantly increased in the strain psm16 group compared to the phytic acid group. The concentrations of copper (P=0.021) and zinc (P=0.017) in liver, calcium (P=0.000), manganese (P=0.000), and zinc (P=0.000) in serum and manganese (P=0.010) and zinc (P=0.022) in kidney were significantly increased in psm16 group, while copper (P=0.007) and magnesium (P=0.001) were significantly reduced. In conclusion, the addition of phytic acid-degrading bacteria psm16 into a diet including phytic acid can affect the content of trace elements in the liver, kidney, and plasma of mice, counteracting the harmful effects of phytic acid.